Speed of cognitive decline in biomarker stratified SCD subgroups. (20th December 2022) - Jessen, Frank; Kleineidam, Luca; Wolfsgruber, Steffen; Spottke, Annika; Brosseron, Frederic; Laske, Christoph; Perneczky, Robert; Schneider, Anja; Wiltfang, Jens; Teipel, Stefan; Bürger, Katharina; Priller, Josef; et al.
Abstract: Background: Subjective cognitive decline (SCD) is associated with an increased risk of cognitive decline and dementia, specifically in cases in the Alzheimer's continuum (amyloid positive, A+). In the present study we tested, if further stratification with additional markers is useful for identifying fast progressors within SCD‐A+. Method: The analysis is based on 170 SCD case of the multicenter memory clinic based DELCODE study in Germany. The following markers were used as predictors of cognitive decline: number of SCDplus criteria, CSF Aß42/Aß42, tTau, pTau181, APOE status and hippocampal volume. The outcome was the preclinical Alzheimer's cognitive composite 5 (PACC5) over up to 5 years. Univariate and multivariate hierarchical regression models were calculated with continuous (a) and dichotomized (b) variables. Result: In the univariate analyses significant or close to significant associations of Aß42/Aß42 (a:p = 0.012; b:p = 0.040), tTau (a:p = 0.034; b:p = 0.053) and pTau181 (a:p = 0.057; b:p = 0.019) with cognitive decline were observed. In the hierarchical model with continuous variables, only Aß42/Aß40 reached significance (p = 0.016); while dichotomized variables Aß42/Aß40 (p = 0, 074) and pTau181 (p = 0.068) reached trend level significance. Conclusion: Within SCD‐A+, those who are also pTau positive show greatest decline. This finding is in agreement with the concept of A+ and T+ indicating full Alzheimer's disease pathology and is important for the design of clinical trials in SCD.